Patient-reported outcomes in high-risk HR+/HER2-early breast cancer patients treated with endocrine therapy with or without palbociclib within the randomized PENELOPEB study - García-Sáenz, José Angel; Marmé, Frederik; Untch, Michael; Bonnefoi, Herve; Kim, Sung-Bae; Bear, Harry; Mc Carthy, Nicole; Gelmon, Karen; Martin, Miguel; Kelly, Catherine M.; Reimer, Toralf; Toi, Masakazu; et al. (European journal of cancer, 2024)
Background: The PENELOPEB trial investigating efficacy and safety of additional 1-year post-neoadjuvant pal-bociclib to standard endocrine therapy (ET) high-risk hormone receptor-positive (HR+)/human epidermal growth factor receptor 2-negative (HER2-) early breast cancer patients failed to improve invasive disease-free survival (iDFS). This analysis compared patient-reported outcomes (PROs) between treatment groups.Patients and methods: Patients received 13 cycles of palbociclib 125 mg/day (n = 631) or placebo (n = 619) orally for 3 out of 4 weeks + ET. European Organization for Research and Treatment of Cancer Quality-of-Life Questionnaire (EORTC QLQ-C30), its breast cancer (BR23) and fatigue (FA13) modules, mood questionnaire GAD7 and European Quality of Life 5 Dimensions (EQ-5D) instruments were used for the assessment of quality of life (QoL). Repeated-measures mixed-effects models were used to evaluate differences in PRO, changes of PRO over time, and treatment-by-time interactions.Results: 924 of 1250 patients (73.9%) completed baseline and at least one post-baseline questionnaire of all PRO instruments. General health status (GHS)/QoL based on EORTC QLQ-C30 was high in both arms (mean [SD]: palbociclib 70.1 [19.3], placebo 71.4 [18.8]) and was slightly higher in the placebo arm (LeastSquare mean difference: 0.82, p < 0.001). Higher fatigue was reported in the palbociclib arm (mean [SD]: 30.3 [23.8] vs. placebo 28.3 [22.7]; p < 0.001). No statistically significant differences were observed among FA13 physical, cognitive, and emotional fatigue subscales.Conclusion: Patient-reported global QoL and fatigue did not substantially change in both treatment arms. Slight differences in GHS, physical functioning, and fatigue favored the placebo arm statistically without achieving clinically meaningful thresholds.
Im Text ist "B" hochgestellt
Gesehen am 30.07.2024
Online veröffentlicht: 5. November 2023, Artikelversion: 23. November 2023